The exceptional teacher : - Aaronsohn, Elizabeth (Ossey-Bass, 2003)
The Uncovered Curriculum addresses three crucial issues in the field of education: What do teachers really want our children to get out of school? How do their past schooling experiences inhibit them from achieving these goals? How can teachers become the courageous and thoughtful leaders our schools need? Using personal narrative and extensive research, Elizabeth Aaronsohn shows how reflective practice can provide students with a more innovative individuals learning experience.